2015
DOI: 10.1016/j.addbeh.2015.01.023
|View full text |Cite
|
Sign up to set email alerts
|

The relation between tobacco taxes and youth and young adult smoking: What happened following the 2009 U.S. federal tax increase on cigarettes?

Abstract: Background On April 1, 2009, the federal government raised cigarette taxes from $0.39 to $1.01 per pack. This study examines the impact of this increase on a range of smoking behaviors among youth aged 12 to 17 and young adults aged 18 to 25. Methods Data from the 2002–2011 National Survey on Drug Use and Health (NSDUH) were used to estimate the impact of the tax increase on five smoking outcomes: (1) past year smoking initiation, (2) past-month smoking, (3) past year smoking cessation, (4) number of days ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 19 publications
3
53
1
Order By: Relevance
“…Bader, Boisclair, and Ferrence 2011;Chaloupka, Straif, and Leon 2011;Nikaj and Chaloupka 2014;Van Hasselt et al 2015; see also Jha and Peto 2015).…”
Section: Adding Situational Cues That Increase the Salience Of Negatimentioning
confidence: 95%
“…Bader, Boisclair, and Ferrence 2011;Chaloupka, Straif, and Leon 2011;Nikaj and Chaloupka 2014;Van Hasselt et al 2015; see also Jha and Peto 2015).…”
Section: Adding Situational Cues That Increase the Salience Of Negatimentioning
confidence: 95%
“…By increasing cigarette prices, cigarette taxes substantially reduce smoking rates and generate large improvements in public health. Research examining the impact of Federal cigarette tax increases on the number of teen or young-adult smokers imply that the 2009 Federal cigarette tax increase will reduce youth smoking by between 3 and 15 percentage points (van Hasselt et al 2015;Huang and Chaloupka 2012;CBO 2012b;Carpenter and Cook 2008). Assuming that roughly a third of youth smokers die prematurely due to smoking (U.S.…”
Section: Box A: Public Health Benefits Of Chipramentioning
confidence: 99%
“…2 According to National Basic Health Research, it is estimated, the prevalence of tobacco smoking increased from 34.2 % in 2007 to 36.3 % in 2013. [3][4][5] The prevalence of smokers in adolescents (aged [15][16][17][18][19] years has increased from 0.7% in 2007 to 11.2% in 2013, as well as among age of 20-24 years increased from 17.3% in 2007 to 27.2% in 2013. The average age of people early smoking in Indonesia is at 17.6 years.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Study in United States found that cigarette tax increase associated with a substantial reduction in smoking among youth and young adultssuch as the odds of smoking initiation decreased, the odds of past-month smoking also decreased, current smokers smoked on fewer days and smoked fewer cigarettes per day after the tax increase. 17 As for study among young adults in Columbia, found that an increase in the price of cigarettes led to transitions from daily smoking to no smoking, from moderate daily to light daily smoking, and from heavy daily smoking to moderate daily smoking. 18 Youth and the poor are more price sensitive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation